Differentiated thyroid cancer. Uruguay 1986. - Delgado, Bolívar; Farre, Iliana; Risi, Leonardo (Cirugía del Uruguay, 1989)
Authors analyse a series of 31 cases of differentiated thyroid carcinomas proceeding from two surgical services in a period of five years, and compare their results with 1974 national series and international data. They point out several significant differences, mostly related to frequency, age, prevailing histological types, evolutionary stages, pre-operative diagnostic evaluation and surgical tactics.